Efecto de la lovastatina sobre la producción de metano y la digestibilidad de la materia seca in vitro del pasto kikuyo (Cenchrus clandestinus) (2015)
ABSTRACT: Emissions of methane (CH4), from cattle rumen fermentation, have a negative impact on the environment and energy balance of animals, increasing global warming and reducing the energy retained, respectively. There is evidence that lovastatin inhibits methanogens growth without affecting other rumen microbial populations. The aim of this study was to determine the effect of increasing levels of lovastatin on in vitro CH4 production and dry matter digestibility (DMD) of kikuyu grass (Cenchrus clandestinus). It was used the in vitro gas production technique, incubing kikuyu grass of 45 days old with four levels of lovastatin (0, 0.01, 0.05, 0.10 mg/ml). At the end of 24 hours, gas and CH4 productions, DMD and fermentation profile was evaluated. A completely randomized design was used for data analysis, through the PROC MIXED SAS procedure. The highest level of lovastatin significantly reduced (p <0.05) the gas and CH4 productions and the DMD. The fermentation profile showed a tendency not defined in terms of levels evaluated, finding a higher concentration of VFA in the treatment 0.05 mg/ml. Although the lovastatin significantly reduces CH4 production, without affecting the DMD equally, this effect was evidenced with higher level than the reported in the literature. Perhaps the answer is conditioned to use of rumen fluid, contrasting with pure cultures of methanogens used in other studies.